A method for rapidly preparing epoxy composite materials by underwater front polymerization and its application
Through UV-induced cutting-edge polymerization technology, combined with the use of CuCl2 and sulfur aluminate cement, the ultra-fast preparation of epoxy composite materials is achieved underwater in situ, solving the problem of rapid preparation of large-volume structural components underwater, and has high mechanical properties and fast curing features.
Patent Information
- Application Number
- CN202410690304.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-05-30
AI Technical Summary
It is difficult to quickly prepare large-volume structural components underwater in the prior art. Traditional polymer concrete takes a long time to achieve structural strength, while thermal curing methods are not energy-saving and difficult to achieve underwater.
UV-induced cutting-edge polymerization technology is adopted to reduce the reaction starting temperature through CuCl2, use sulfur aluminate cement to improve long-term performance, and regulate the consistency by gas-phase silica, so as to achieve ultra-fast preparation of epoxy composites in situ underwater.
It realizes super-fast underwater curing, fast polymerization speed, and self-propagation rate reaching 41.6mm min-1. The prepared epoxy composite material has excellent mechanical properties, can instant compressive strength and bending strength, and can be used for Underwater in situ bonding a variety of materials.
Smart Images

Figure CN118580819B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and relates to a method for preparing an epoxy composite material and an application thereof, and specifically to a method for ultra-fast preparation of an epoxy composite material by underwater in-situ UV-initiated front polymerization and an application thereof in an adhesive. Background Art
[0002] With the continuous reduction of land resources and the growing demand for marine engineering, the development of underwater engineering has become an important aspect of modern construction. At present, the polymer concrete material system is mainly used for the in-situ preparation of large-volume structural components underwater. However, this modified polymer concrete, similar to traditional concrete, still requires a long cement hydration time to provide the required strength of the structure. In contrast, epoxy resin system, a thermosetting polymer composite material, is widely used due to its excellent mechanical properties, electrical insulation properties, adhesion, heat resistance and corrosion resistance. The synthesis of polymer composites involves room temperature curing, light curing and thermal curing, the latter two of which have much faster molding time than traditional concrete materials. For example, photocurable polymers usually reach their final strength within a few minutes. Nevertheless, due to the limited penetration of ultraviolet light, the cured thickness is generally in the millimeter range. Thermal curing requires a large amount of heat source and is an energy-inefficient curing method. In addition, it is difficult to reach the ambient temperature required for polymer thermal curing underwater. Therefore, the composite material preparation technology for rapid underwater preparation of large-volume structural components still needs to be improved.
[0003] Interestingly, polymer adhesives are being developed for a variety of underwater bonding applications, including hull repair, metal bonding, and modifying marine structures. However, for most underwater structural adhesive applications, the immersed adhesive needs to be pulled out of the water and a dry environment is created at the application site to achieve higher bonding strength. Adhesives have low adhesion to wet surfaces, and in most cases, bonding is achieved with a dry surface. Nevertheless, some cases may require the application of adhesives underwater. In addition, most adhesives are used when the bonded materials need to be clamped. The above research has made important contributions to the realization of underwater in-situ bonding. However, it is still limited to objective conditions, such as full-area UV irradiation and clamping process, which has great limitations in practical application. It is also challenging to use the above adhesives to prepare large-volume structural components underwater. In addition, underwater rapid plugging has good application prospects. Therefore, it is very necessary to develop a new polymer composite system that can quickly form and bond multiple materials in situ underwater.
[0004] Frontal polymerization driven by polymerization exotherm is a synthetic method with important advantages and development potential. It makes full use of the heat energy released by the polymerization reaction, which is usually considered to be wasted and unused, to provide a local heat source for the subsequent polymerization process and maintain the continuous occurrence of the reaction. The only external injected energy required for frontal polymerization is the initial thermal (or light) stimulation of the local ignition reaction. This method has the advantages of fast curing, no spatial restrictions, and energy saving. It has been widely studied and applied to various monomers such as (meth)acrylates, acrylamide, and dicyclopentadiene. At present, the application of free radical induced cationic frontal polymerization (RICFP) in the preparation of epoxy resin composites has been put on the agenda. In addition, there are few studies on the application of UV-induced self-propagating polymerization in underwater in-situ synthesis. Summary of the invention
[0005] The purpose of the present invention is to provide a method for rapidly preparing epoxy composite materials by underwater front polymerization and its application. The method uses UV to initiate front polymerization to prepare epoxy composite materials in situ ultra-rapidly. The addition of CuCl2 can effectively reduce the reaction starting temperature of the system. It has the characteristics of low-temperature polymerization and fully improves the polymerization degree of monomers in the actual bonding process. The addition of sulphoaluminate cement improves the characteristics of long-term underwater performance without degradation. Fumed silica is used to adjust the consistency and does not affect the front polymerization degree. The entire polymerization process is completed within a few minutes, and the underwater self-propagation speed reaches 41.6mm min -1 , which provides a new idea for underwater in-situ ultra-fast synthesis of high-strength epoxy-based composites and underwater in-situ bonding.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] An epoxy premix slurry for underwater front polymerization is prepared by uniformly mixing the following raw materials in a weight ratio: component A, 1.0; component B, 1.0; carbon fiber, 0-0.04; fumed silica, 0-0.05; cement, 0-0.4; quartz sand, 0-0.6, wherein:
[0008] Component A is prepared by uniformly mixing the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 0.8-1.2; 3-ethyl-3-oxetanol (EOM), 0-0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0-0.1;
[0009] Component B is prepared by uniformly mixing the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 0.8-1.2; 3-ethyl-3-oxetanol (EOM), 0-0.375; benzopinacol (TPED), 0-0.2; CuCl2.2H2O, 0.002-0.006;
[0010] The length of the carbon fiber is 1 mm;
[0011] The cement is 62.5 sulphoaluminate cement;
[0012] The quartz sand particle size is 14 to 70 meshes.
[0013] A method for rapidly preparing epoxy composite materials by underwater front polymerization comprises the following steps:
[0014] Step (1) weighing BADGE, EOM, CE and IOC-8SbF6 according to the weight ratio, and ultrasonically dispersing for 30 to 60 minutes to obtain component A;
[0015] Step (2) weighing BADGE, EOM, CE, TPED and CuCl2.H2O according to a weight ratio, and ultrasonically dispersing for 30 to 60 minutes to obtain component B;
[0016] Step (3) weighing BADGE, EOM, CE and TPED according to the weight ratio, and ultrasonically dispersing for 30 to 60 minutes to obtain component B-0;
[0017] Step (4) mixing the A / B components in a weight ratio of 1:1 and adding carbon fiber, fumed silica, cement and quartz sand by weight, and mechanically stirring until the mixture is uniform to obtain an epoxy premix slurry;
[0018] Step (5) injecting the epoxy premix slurry into the interface of the underwater bonded materials or into the mold using a syringe;
[0019] Step (6) excites one end of the epoxy premix slurry by irradiating it with a 365nm UV lamp for 10 to 60 seconds until polymerization begins, wherein the irradiated area uses 0.5 to 2 ml of a transparent premix solution of A / B-0 components mixed in a weight ratio of 1:1 to ensure sufficient excitation of polymerization.
[0020] The epoxy composite material prepared by the above method has excellent mechanical properties and can be used as an adhesive for underwater in-situ bonding of glass, low-carbon steel, aluminum, and ceramics.
[0021] Preparation principle:
[0022] The present invention uses BADGE as a reaction monomer, CE and EOM as reactive diluents to improve the fluidity of the premixed solution to improve workability, IOC-8SbF6 as a photoinitiator, and TPED as a thermal initiator. Figure 1 As shown, the photoinitiator is cleaved by UV irradiation and forms a cation. This cation extracts a proton from the monomer or solvent to form a highly reactive superacid, which reacts with the monomer to form a polymer and generates heat. The generated heat, which is often overlooked or wasted in traditional polymerization processes, then cleaves the thermal radical initiator to produce reactive radicals that can cleave the cationic photoinitiator and form further acid. If the polymerization heat reaches the temperature at which TPED cleaves, steps III and II continue until the monomer reaction is complete. In addition, the addition of CuCl2 reduces the activation energy of the ring-opening polymerization reaction. The detailed catalytic process is Cu 2+ It forms a coordination bond with the O of the epoxy group, reducing the activation energy required for the ring-opening polymerization of the epoxy group, thereby reducing the energy barrier of the reaction and further reducing the starting temperature of the polymerization, such as Figure 2 shown.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1) The whole process only requires a short period of UV irradiation, and the entire self-propagating process does not require the injection of external energy.
[0025] 2) The epoxy premix slurry has the characteristics of underwater non-dispersion and successful underwater self-propagation.
[0026] 3) It has the characteristics of underwater controllable ultra-fast curing, fast polymerization speed, and can reach the final strength in a short time. The underwater self-propagation rate is 41.6mm min -1 .
[0027] 4) The instant compressive strength and flexural strength of the polymer composites prepared by underwater in-situ frontal polymerization reach 78MPa and 20MPa.
[0028] 5) Epoxy adhesives can bond glass, mild steel, aluminum, and ceramics underwater in situ within 1 day through front polymerization. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the schematic diagram of UV-induced frontal polymerization reaction.
[0030] Figure 2 This is the catalytic mechanism of CuCl2 on epoxy groups.
[0031] Figure 3 It is a schematic diagram of compression shear strength test;
[0032] Figure 4is a schematic diagram of bending strength test;
[0033] Figure 5 This is an optical photograph of a specimen prepared by underwater in-situ frontal polymerization;
[0034] Figure 6 is the temperature distribution of the underwater front polymerization process. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below in conjunction with the accompanying drawings, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0036] The present invention provides an epoxy premix slurry for underwater front polymerization, which is uniformly mixed with the following raw materials in weight ratio: component A, 1.0; component B, 1.0; carbon fiber, 0-0.04; fumed silica, 0-0.05; cement, 0-0.4; quartz sand, 0-0.6, wherein:
[0037] Component A is prepared by uniformly mixing the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 0.8-1.2; 3-ethyl-3-oxetanol (EOM), 0-0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0-0.1;
[0038] Component B is prepared by uniformly mixing the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 0.8-1.2; 3-ethyl-3-oxetanol (EOM), 0-0.375; benzopinacol (TPED), 0-0.2; CuCl2.2H2O, 0.002-0.006;
[0039] The length of the carbon fiber is 1 mm;
[0040] The cement is 62.5 sulphoaluminate cement;
[0041] The quartz sand particle size is 14 to 70 meshes.
[0042] The raw material ratio is used in the process of making epoxy premix slurry, and the weight error of all raw materials is controlled within "±" 0.5%.
[0043] When preparing the epoxy composite material according to the present invention, the raw materials are prepared according to the raw material ratio, and an ultrasonic instrument is required. The specific steps are as follows:
[0044] Step (1) weighing BADGE, EOM, CE and IOC-8SbF6 according to the weight ratio, and ultrasonically dispersing for 30 to 60 minutes to obtain component A;
[0045] Step (2) weighing BADGE, EOM, CE, TPED and CuCl2.H2O according to a weight ratio, and ultrasonically dispersing for 30 to 60 minutes to obtain component B;
[0046] Step (3) weighing BADGE, EOM, CE and TPED according to the weight ratio, and ultrasonically dispersing for 30 to 60 minutes to obtain component B-0;
[0047] Step (4) mixing the A / B components in a weight ratio of 1:1 and adding carbon fiber, fumed silica, cement and quartz sand by weight, and mechanically stirring until the mixture is uniform to obtain an epoxy premix slurry;
[0048] Step (5) injecting the epoxy premix slurry into the interface of the underwater bonded materials or into the mold using a syringe;
[0049] Step (6) excites one end of the epoxy premixed slurry by irradiating with a 365nm UV lamp for 10 to 60 seconds until polymerization begins, wherein the irradiated area uses 0.5 to 2 ml of a transparent premixed solution of A / B-0 components mixed in a weight ratio of 1:1 to ensure sufficient excitation of polymerization. The polymer composite material obtained by the above steps is as follows Figure 5 shown.
[0050] When preparing the epoxy composite material, the present invention adopts an A / B two-component form, can be stored for a long time at 4°C, and only needs simple mechanical stirring when in use; the ultrasonic treatment does not need to control the temperature range; the epoxy composite material has underwater non-dispersibility and underwater self-propagation characteristics, and can be used as an adhesive to bond glass, low-carbon steel, aluminum, and ceramics in situ underwater.
[0051] The present invention uses BADGE as a monomer and divides the epoxy premix solution into two components, A / B, which effectively avoids prepolymerization. By adding fillers such as cement, aggregate, fiber, and fumed silica, the amount of chemical adhesives used is reduced and durability is enhanced. The entire underwater in-situ polymerization process is completed within a few minutes. This in-situ underwater polymerization strategy provides a new material basis and preparation process for ultra-fast preparation of structural materials, in-situ repair, 3D printing, etc.
[0052] Embodiment 1:
[0053] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; carbon fiber, 0.04; fumed silica, 0.04; cement, 0.4; quartz sand, 0.6, of which:
[0054] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0055] The B component is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015;
[0056] The length of the carbon fiber is 1 mm;
[0057] The cement is 62.5 sulphoaluminate cement;
[0058] The particle size of the quartz sand is 14 to 70 meshes.
[0059] Embodiment 2:
[0060] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; carbon fiber, 0.04; cement, 0.02, of which:
[0061] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0062] The B component is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015;
[0063] The length of the carbon fiber is 1 mm.
[0064] The cement is 62.5 sulphoaluminate cement.
[0065] Embodiment 3:
[0066] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; carbon fiber, 0.04; cement, 0.04, of which:
[0067] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0068] The B component is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015;
[0069] The length of the carbon fiber is 1 mm;
[0070] The cement is 62.5 sulphoaluminate cement.
[0071] Embodiment 4:
[0072] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; carbon fiber, 0.04; cement, 0.06, of which:
[0073] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0074] The B component is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015;
[0075] The length of the carbon fiber is 1 mm;
[0076] The cement is 62.5 sulphoaluminate cement.
[0077] Embodiment 5:
[0078] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; fumed silica, 0.1, wherein:
[0079] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0080] The B component is uniformly mixed by the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015.
[0081] Embodiment 6:
[0082] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; fumed silica, 0.2, wherein:
[0083] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0084] The B component is uniformly mixed by the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015.
[0085] Embodiment 7:
[0086] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; fumed silica, 0.3, wherein:
[0087] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0088] The B component is uniformly mixed by the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015.
[0089] Embodiment 8:
[0090] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; fumed silica, 0.4, wherein:
[0091] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0092] The B component is uniformly mixed by the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015.
[0093] Embodiment 9:
[0094] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; fumed silica, 0.5, wherein:
[0095] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0096] The B component is uniformly mixed by the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015.
[0097] Comparative Example 1:
[0098] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; carbon fiber, 0.04; fumed silica, 0.04; quartz sand, 0.6, of which:
[0099] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0100] The B component is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015;
[0101] The length of the carbon fiber is 1 mm;
[0102] The quartz sand particle size is 14 to 70 meshes.
[0103] Comparative Example 2:
[0104] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; carbon fiber, 0.02, of which:
[0105] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0106] The B component is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015;
[0107] The length of the carbon fiber is 1 mm.
[0108] Comparative Example 3:
[0109] The epoxy premix slurry for underwater front polymerization is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0, wherein:
[0110] The component A is uniformly mixed with the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate (IOC-8SbF6), 0.1;
[0111] The B component is uniformly mixed by the following raw materials according to weight ratio: bisphenol A diglycidyl ether (BADGE), 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (CE), 1.125; 3-ethyl-3-oxetanol (EOM), 0.375; benzopinacol (TPED), 0.2; CuCl2.2H2O, 0.015.
[0112] According to ASTM C293 M-10 and ASTM D5045-99, the compressive strength test loading rate is 2.4 kN s -1 The specimen size is 20 mm × 20 mm × 20 mm, and the loading rate for the flexural strength and compression shear tests is 1 mm min -1 ,like Figure 3 and Figure 4 As shown in the figure, the size of the bonded material is 20mm×40mm×10mm, and the bonding thickness is 4mm.
[0113] Frontal polymerization was carried out underwater and above water on Example 1 and Comparative Example 1, and the obtained specimens were subjected to bending strength and compressive strength tests. The results are shown in Tables 1 and 2.
[0114] Table 1
[0115]
[0116] Table 2
[0117]
[0118] It can be seen from Tables 1 and 2 that the flexural and compressive strengths of the test specimens prepared in accordance with Example 1 on water reached 29.1 MPa and 80 MPa. Compared with the blank control group (Comparative Example 1), the addition of sulphoaluminate cement significantly improved the underwater durability of the polymer composite material and the ability to maintain long-term underwater mechanical properties without deterioration. After 28 days, the flexural strength and compressive strength of Example 1 were 13.6% and 21.8% higher than those of the control group. The flexural strength and compressive strength of Comparative Example 1 deteriorated by 23.3% and 19.5% respectively after 28 days of underwater immersion. The temperature field of the self-propagating process was measured by thermocouples as shown in Figure 6 As shown, the self-propagation rate reaches 41.6 mm min -1 .
[0119] The compressive shear strength test was carried out on Examples 2 to 4 and Comparative Example 2. The results are shown in Table 3.
[0120] Table 3
[0121]
[0122]
[0123] As can be seen from Table 3, the epoxy composite material prepared in situ by frontier polymerization underwater can be successfully bonded to steel, aluminum, ceramics and glass within one day. Compared with the blank control group (Comparative Example 2), the addition of an appropriate amount of sulphoaluminate cement significantly improves the underwater durability of the epoxy-based adhesive and the performance of maintaining the underwater long-term mechanical properties without deterioration. After 28 days of underwater immersion, the bonding of Comparative Example 2 to steel even failed.
[0124] The premixed solutions before the front polymerization of Examples 5 to 9 and Comparative Example 3 were subjected to a rotational viscosity test. The results are shown in Table 4.
[0125] Table 4
[0126]
[0127]
[0128] From the results in Table 4, it can be seen that fumed silica can significantly increase the consistency of the epoxy premix solution, thereby effectively avoiding aggregate segregation.
Claims
1. An epoxy premix slurry for underwater front polymerization, characterized in that The epoxy premix slurry is uniformly mixed with the following raw materials according to weight ratio: component A, 1.0; component B, 1.0; carbon fiber, 0-0.04; fumed silica, 0-0.05; cement, 0-0.4; Quartz sand, 0~0.6, including: Component A is prepared by uniformly mixing the following raw materials in a weight ratio: bisphenol A diglycidyl ether BADGE, 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate CE, 0.8-1.2; 3-ethyl-3-oxabutane methanol EOM, 0.375; 4-octyloxydiphenyliodonium hexafluoroantimonate IOC-8 SbF6, 0.1; Component B is prepared by uniformly mixing the following raw materials in a weight ratio: bisphenol A diglycidyl ether BADGE, 1.0; 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate CE, 0.8-1.2; 3-ethyl-3-oxetanol EOM, 0.375; benzopinacol TPED, 0.2; and CuCl2.2H2O, 0.002-0.
006.
2. The epoxy premix slurry for underwater front polymerization according to claim 1, characterized in that The length of the carbon fiber is 1 mm.
3. The epoxy premix slurry for underwater front polymerization according to claim 1, characterized in that The cement is 62.5 sulphoaluminate cement.
4. The epoxy premix slurry for underwater front polymerization according to claim 1, characterized in that The quartz sand particle size is 14-70 meshes.
5. A method for preparing epoxy composite materials by underwater front polymerization, characterized in that The method comprises the following steps: Step (1) weighing bisphenol A diglycidyl ether BADGE, 3-ethyl-3-oxetanol EOM, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate CE, and 4-octyloxydiphenyliodonium hexafluoroantimonate IOC-8 SbF6 according to the weight ratio of claim 1, and ultrasonically dispersing to obtain component A; Step (2) weighing bisphenol A diglycidyl ether BADGE, 3-ethyl-3-oxetanol EOM, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate CE, benzopinacol TPED, and CuCl2.H2O according to the weight ratio of claim 1, and ultrasonically dispersing to obtain component B; Step (3) mixing the A / B components in a weight ratio of 1:1, adding carbon fiber, fumed silica, cement, and quartz sand in the weight ratio according to claim 1, and mechanically stirring until uniform, to obtain an epoxy premix slurry; Step (4) injecting the epoxy premix slurry into the interface of the underwater bonded materials or into the mold using a syringe; Step (5) excites one end of the epoxy premix slurry by irradiating it with a 365 nm UV lamp for 10 to 60 seconds until polymerization begins.
6. The method for preparing epoxy composite materials by underwater front polymerization according to claim 5, characterized in that In the step (5), 0.5-2 ml of A / B-0 components are mixed uniformly with a transparent epoxy premix slurry in a weight ratio of 1:1 in the irradiation area to ensure sufficient polymerization. The B-0 component is made by mixing the following raw materials uniformly in a weight ratio: BADGE, 1.0; CE, 0.8-1.2; EOM, 0~0.375; TPED, 0.
2.
7. Use of the epoxy composite material prepared by the method according to any one of claims 5 to 6 in adhesives.
8. The use of the epoxy composite material in an adhesive according to claim 7, characterized in that The adhesive can be used for underwater in-situ bonding of glass, mild steel, aluminum, and ceramics.
Citation Information
Patent Citations
Preparation method of epoxy mortar for filling ocean oil and gas pipeline
CN103819144A
Cation-curable resin composition
CN108291012A